Kepemimpinan Etikal dan Komunikasi terhadap Kinerja Pegawai - Yeti Maisaroh; Muhlis Hafel; Syahruddin Hattab (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine ethical leadership and communication together on employee performance at the West Papua Regional Office of the Ministry of Law and Human Rights. This research uses a quantitative approach because it is objective in testing hypotheses. This research was carried out at the West Papua Ministry of Law and Human Rights Regional Office. Data collection techniques include observation, interviews, and questionnaires using descriptive statistical data analysis techniques. The research results, simultaneously that communication and Ethical Leadership have a significant influence on Employee Performance. Improved Communication and Ethical Leadership will increase Employee Performance on average. A positive regression coefficient value indicates that the relationship between the independent variable and the dependent variable is positive. This means that increasing the independent variable will increase the dependent variable. A large regression coefficient value indicates that the influence of the independent variable on the dependent variable is greater. In conclusion, Ethical Leadership and Communication have a significant and positive influence on Employee Performance. Keywords: Communication, Employee Performance, Ethical Leadership.